0.67‐μm2 /bitcell two‐transistor leakage‐based physically unclonable function with native bit‐instability of 0.89% at 65 nm. Issue 23 (9th October 2020) - Li, Gang; Wang, Pengjun; Ma, Xuejiao; Chen, Bo
Abstract : A compact and robust physically unclonable function (PUF) for secure key generation is proposed. With the help of a cross‐coupled amplifier, the leakage‐current mismatch between the two transistors was digitised to produce a unique chip identification. The measurement results show that the proposed PUF has the best‐in‐class randomness and uniqueness, as well as the following features: (i) an ultra‐small PUF cell with a minimum feature size of 159 F 2, being the lowest reported to date in CMOS, (ii) a low native BER (bit‐instability) of 0.16% (0.89%) was measured at the golden condition, and (iii) an autocorrelation of 0.007 at 95% confidence was achieved.